Effect of Oxidation Agents on Photo-Decolorization of Vitamin B12 in the Presence of ZnO/UV-A System - Luma Majeed Ahmed; Shaymaa Ibrahim Saaed; Ashraff Aziz Marhoon (Indonesian Journal of Chemistry, 2018)
The aim of this work was to apply the many various oxidation agents namely H2O2, K2S2O8 and Fe2+ on the aqueous solution of vitamin B12 with the presence of ZnO. The results indicated that the use of the mixture of H2O2 and K2S2O8 in suspension of vitamin B12 and ZnO gave a maximum efficiency percentage about 95.85% in 12 min; it was higher than that without the addition of oxidation reagent 79.33% in the same time. The obtained results demonstrated that the activation energy for this photoreaction without the addition of oxidation agent was more than that the apparent activation energy value with the used mixture of H2O2 and K2S2O8. The thermodynamic study showed that both reactions were endothermic, less-random and non-spontaneous. The ΔH# with the oxidant agents (31.43 kJ mol-1) is less than that without using oxidant agents (35.81 kJ mol-1). Moreover, the addition of series of oxidant agent solution to vitamin B12 solution led to change the photocatalytic activity for decolorization of vitamin B12 in suspension solution of ZnO, and was found the activity sequence as follows: (H2O2 + K2S2O8) > (H2O2 + Fe(II)) (Fenton reaction) > (H2O2) > (K2S2O8) > (without the oxidation agents) > (K2S2O8 + Fe(II)) > Fe(II).